Teaching Object-Oriented Programming is more than teaching: Object-Oriented Programming Languages - Knudsen, Jørgen Lindskov; Madsen, Ole Lehrmann (DAIMI Report Series, 1988)
One of the important obligations of an expanding research area is to discuss how to approach the teaching of the subject. Without this discussion, we may find that the word is not spread properly, and thus that the results are not properly utilized in in dustry. Furthermore, discussing teaching the research area gives additional insight into the research area and its underlying theoretical foundation. In this paper we will report on our approach to teaching programming languages as a whole and especially teaching object-oriented programming. The prime message to be told is that working from a theoretical foundation pays off. Without a theoretical foundation, the discussions are often centered around features of different languages. With a foundation, discussions may be conducted on solid ground. Furthermore, the students have significantly fewer difficulties in grasping the concrete programming languages when they have been presented with the theoretical foundation than without it.